'But I've been teaching for 20 years…': encouraging teaching accreditation for experienced staff working in higher education. Issue 3 (2nd July 2016) - Spowart, Lucy; Turner, Rebecca; Shenton, Deborah; Kneale, Pauline
Abstract : The status of teaching and learning is an issue those providing and supporting higher education grapple with. The UK Higher Education Academy offers accreditation aligned to the professional standards framework (PSF). The PSF contextualises the role of teaching and supporting learning, and offers a mechanism for individuals' commitment to be recognised. Here, we present a case-study of 19 established academics who reflected on their experiences of gaining recognition through their university's accreditation scheme. Respondents prioritised institutional structures and outcomes such as student recruitment, job security, and status as drivers for engagement. Institutional leadership was significant in driving the accreditation agenda.